2001
DOI: 10.1097/00008571-200110000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in human CYP2C8 decrease metabolism of the anticancer drug paclitaxel and arachidonic acid

Abstract: Cytochrome P450 (CYP) 2C8 is the principal enzyme responsible for the metabolism of the anti-cancer drug paclitaxel (Taxol). It is also the predominant P450 responsible for the metabolism of arachidonic acid to biologically active epoxyeicosatrienoic acids (EETs) in human liver and kidney. In this study, we describe two new CYP2C8 alleles containing coding changes: CYP2C8*2 has an Ile269Phe substitution in exon 5 and CYP2C8*3 includes both Arg139Lys and Lys399Arg amino acid substitutions in exons 3 and 8. CYP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
387
5
14

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(424 citation statements)
references
References 37 publications
18
387
5
14
Order By: Relevance
“…Initial in vitro studies for CYP2C8*3 suggested a lower activity, 31,32 but more recent studies in healthy volunteers have repeatedly demonstrated an increased metabolizing capacity for this allele. [33][34][35][36] In contrast, CYP2C8 haplotype C 35,41 and CYP3A5*3 37 confer a reduced activity.…”
Section: Discussionmentioning
confidence: 99%
“…Initial in vitro studies for CYP2C8*3 suggested a lower activity, 31,32 but more recent studies in healthy volunteers have repeatedly demonstrated an increased metabolizing capacity for this allele. [33][34][35][36] In contrast, CYP2C8 haplotype C 35,41 and CYP3A5*3 37 confer a reduced activity.…”
Section: Discussionmentioning
confidence: 99%
“…The study was initiated based on reports on CYP2C8*3 as having decreased paclitaxel metabolism 20,21 and reports of a functional significance of ABCB1 SNPs with particular interest in C1236T, G2677T/A and C3435T; 22-24 the other candidate SNPs entered the study after it was initiated but the a priori distinction between confirmative and exploratory candidates was kept to meet the issue of multiple testing.…”
Section: Introductionmentioning
confidence: 99%
“…Además, la enzima CYP2C8 muestra gran variación entre los individuos en el metabolismo de sustratos (36) y presenta diferentes variantes genéticas (37,38). Todos estos factores pueden ayudar también a explicar la falta de concordancia entre los resultados in vivo e in vitro con la amodiaquina.…”
Section: Discussionunclassified
“…En un estudio de nuestro grupo de 69 pacientes de tres municipios con paludismo de Colombia (Tumaco, Turbo y El Bagre), se encontró la variante CYP2C8*2 en 6% de los pacientes y la mutación R139K de la variante CYP2C8*3 en 3%; dichas variantes aparecieron principalmente en los pacientes en quienes hubo falla terapéutica de la monoterapia con amodiaquina (39); además, se sabe que la presencia de estas mutaciones reduce el metabolismo del paclitaxel (medicamento anticanceroso) y del ácido araquidónico (38).…”
Section: Discussionunclassified